Cultural Capital and Learning Orientation: A Sociological Examination of the Relationship Between Family Habitus, Personality, and Academic Achievement - Isrizal, Isrizal; Neviyarni, Neviyarni; Mudjiran, Mudjiran (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
This study aims to explore the complex relationship between cultural capital, personality, and academic achievement in the context of the sociology of education. Through a qualitative approach based on a comprehensive literature study, the study analyzes the mechanisms of cultural transmission and their implications for individual learning orientations. The research method uses meta-qualitative analysis with systematic literature review techniques, conducting a systematic review of academic sources related to cultural capital and education. The data collection process was carried out through searching academic databases, with inclusion criteria based on theme relevance and publication quality. The results of the study revealed three main findings: (1) Cultural capital plays a fundamental role in shaping learning orientations through the mechanism of family cultural transmission; (2) Academic personality is a social construction formed through dynamic interactions between social structures; (3) The education system operates as an arena for the reproduction and transformation of cultural capital. The study recommends the development of a pedagogical approach that is sensitive to the diversity of cultural capital, with a focus on inclusive strategies that accommodate individual differences. Systemic transformation is needed in educational practices to reduce structural inequalities. The main contribution of this study is a holistic conceptual model that integrates sociological and psychological perspectives in understanding the dynamics of education, opening up space for more contextual and equitable pedagogical interventions.